Opioid Prescribing for Noncancer Patients-Issues of Drug Therapy Safety: Results from a German Study Based on Routine Data - Veronika Lappe; Daniel Grandt; Ursula Marschall; Ingrid Schubert (MDPI AG, 2024)
Opioids are highly effective drugs but need close monitoring to avoid harm to patients. The aim of this study was to analyze how guideline recommendations are met for (i) the avoidance of the concomitant use of anxiolytics, hypnotics, or sedatives; (ii) the prescribing of laxatives in long-term opioid treatment; (iii) the co-prescribing of drugs to control the emetic effect of opioids; (iv) pretreatment with non-opioids; and (v) screening for depression when initiating opioids. The results are based on a routine data analysis of a large German health insurance fund. Different study populations of noncancer patients (18+ years old) treated with opioids were analyzed: 10.4% of the opioid recipients in 2021 received at least one concomitant prescription with anxiolytics, hypnotics, or sedatives; 69.3% of those with long-term opioid treatment received at least one laxative prescription. Of those with first-time opioid prescriptions, 4.8% received an antiemetic drug; 47.3% of those with a newly initiated opioid therapy received a non-opioid prescription within three months before the start of the opioid therapy; and 22.0% of patients with incident opioid prescription had at least one documentation of a depression diagnosis within three months of the first prescription. There is an urgent need to improve opioid prescribing to avoid risky combinations and adverse effects.